THE PROFILE OF VAGINAL TEMPERATURE AND CYTOLOGY OF VAGINAL SMEAR IN BALI CATTLE DURING ESTRUS CYCLE PHASE - P.N., Indira; Kustono, K.; Ismaya, I. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
The objective of the study was to evaluate physiological condition of Bali cattle during estrus. Ninecattles were used in the research. The method of the research was descriptive analysis. The measurementof vaginal temperature was conducted by using digital thermometer and cytology of vaginal smear wasdone by using cotton bud swabbed on object glass. It was washed by methanol and was stained withGiemsa staining and was observed by microscope. The results indicated that vaginal temperature were38.39 ± 0.29 oC; 38.05 ± 0.15 oC; 37.4 ± 0.74 oC; 37.86 ± 0.3 oC at estrus, metestrus, diestrus, proestrusphase, respectively. On the basis of the cytology of vaginal smear, estrus phase had more superficialcornification and intermediate cells causing estrogen concentration increased. In conclusion, the profileof vaginal temperature showed that each kind of estrus cycle phase had characteristic within estrus. Thecytology of vaginal smear showed various types of cells preferences in different phase of estrus cycle.